DAMPAK GAME MOBILE LEGEND TERHADAP PERILAKU SOSIAL EMOSIONAL DAN SPIRITUAL ANAK USIA REMAJA KELURAHAN KARYAMULYA KOTA CIREBON - Arib Mubarok; Suklani Suklani (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
One of the sophistication of technology in the internet network is online games. Advances in technology, especially the virtual world, have created millions of games that have been produced. One of the impacts of the mobile legends online game is the loss of a sense of social concern for teenagers towards the surrounding environment. Some teenagers today have an indifferent attitude to the environment. This can be seen directly when there is a social problem. The negative impact of the game can have implications for the identity process of adolescents by being individualistic. The objectives of this study are 1) Teenagers and Mobile Legend Online Games 2) Social Emotional and Spiritual Attitudes of Adolescents. The results of his research are how to anticipate bad things from games, namely: first, frequency, which is related to how often a person engages in online game playing activities within a specified time span. Second, duration is the length of playing time used to play online games, the more time spent playing games, to indicate the longer someone plays online games. Third, full attention, namely the level of concentration on playing online games so that it overrides other things such as eating, bathing, going to school, and not caring about those around them when playing games. Fourth, emotions which include feelings of happiness, sadness, fear, hope, anger, despair.